Effects of deindividuation, removal of responsibility and coaction on impulsive and cyclical aggression - Ploutzian, Raymond F. (2001)
The influence of two deindividuating variables, altered responsibility and coaction in groups, on one's tendency to deliver noxious or helpful stimulation impulsively and in a cyclical pattern to a target person was investigated in a laboratory experiment with use of 96 male and female junior college students. Analysis of variance revealed that, as hypothesized, Ss who coacted in groups of three and who had the responsibility for their behavior removed delivered noxious (but not helpful) stimuli more impulsively than Ss who worked alone and were made to feel responsible (p less than .01). Ss responded in a more cyclical pattern which delivering aversive tones than when delivering facilitating tones (p less than .005). A marginally significant finding was that Ss in groups responded in a more cyclical pattern than Ss alone only when the response was seen as aversive. It was concluded that the probability of impulsive and cyclical aggression may be increased by altered responsibility and coaction.
Includes bibliographical references.
Keywords: Group decision making; Responsibility; Aggressiveness